Social Crowdfunding: a New Model for Financing Regional Development? - Bernardino, Susana (2018)
Crowdfunding is an increasingly attractive source to fund social projects. However, to our best knowledge, the study of crowdfunding for social purposes has remained largely unexplored in the literature. This research envisages a detailed examination of the role of crowdfunding on the early-stage of the social projects at regional level. By comparing the characteristics of the projects available in the Portuguese Social Stock Exchange platform with others that did not use this source of financial support, we envisage to show the critical role of crowdfunding on regional development. The use of inferential techniques (Chi-square test, the Cramer’s V statistic, the Goodman and Kruskal λ and the odds ratio) demonstrates that the use of the Portuguese Social Stock Exchange platform was linked to the geographical location of the social venture as well as its geographical scope. Also, social ventures located on rural regions are more likely to use social crowdfunding platforms than social ventures located in urban areas. Further, the circumstance of having the social ventures acting at a local or regional level seems to be strongly associated with the possibility of using crowdfunding for financing social projects.